Analysis of Public Servant Workload in a Gender Perspective - Marwan, Syaiful (AGENDA: Jurnal Analisis Gender dan Agama, 2022)
Writing this article aims to look at the dynamics of performance development and analysis of the tasks carried out by each individual citizen from a gender perspective between men and women in their work as civil servants in Indonesia. The method developed is a qualitative method with an analysis of literature studies related to the implementation of the work of civil servants, both women and men in Indonesia. The findings obtained are how the performance of women has more variety and uniqueness than the performance of male employees. With variations in the form of responsibility, in this case it shows that in terms of the concept of work, the demands of men are higher in carrying out tasks because most men are responsible for sustaining family life, but the workload provided by the government always pays attention to aspects of gender needs. for each individual civil servant.